Faktor-Faktor yang Berhubungan dengan Kejadian Penyakit Jantung Koroner di Rumah Sakit Pendidikan Prof. dr. Chairuddin P. Lubis Medan Tahun 2025 - Adelia Sembiring; Rahayu Lubis (Pusat Riset dan Inovasi Nasional, 2025)
Coronary heart disease (CHD) is characterized by heart attacks caused by atherosclerosis. In 2024 at Prof. dr. Chairuddin P. Lubis Teaching Hospital Medan, it was 178 people (31%) were productive age patients with CHD receiving outpatient treatment. The purpose of the study was to determine the factors associated with the incidence of CHD in patients aged 25-59 years at Prof. dr. Chairuddin P. Lubis Teaching Hospital Medan in 2025. This study uses quantitative research with Cross Sectional. Sampling technique used accidental sampling with total 82 respondents. Data were collected through interviews using questionnaires and medical records. The results of the bivariate analysis with the chi-square test showed that factors related with CHD were age (p=0,007), gender (p=0,004), physical activity (p=0,022), smoking habits (p=0,009), hypertension (p=0,017), diabetes melitus (p=0,032), and cholesterol levels (p=0,003). There is no relationship between family history (p=0,734) and incidence of CHD. Recommendations for people of productive age to control the risk factors of CHD by regularly doing physical activity, not smoking, and periodically checking for blood pressure, blood sugar, and cholesterol levels.